Mari Winsor's lower body pilates [videorecording (DVD)] - Winsor, Mari (Distributed by Gaiam Americas, Inc., 2012)
Master Pilates instructor Mari Winsor brings 3 dynamic practices focused on areas of the body that her devoted followers have asked for most: hips, thighs, and glutes. Mari's targeted workouts are guaranteed to lengthen, strengthen, and tone trouble areas, resulting in trimmer legs, a tighter waist, and a beautifully defined backside.